2021
DOI: 10.1186/s12909-021-02607-w
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication technology to enhance continuing professional development (CPD) and continuing medical education (CME) for Rwanda: a scoping review of reviews

Abstract: Background Access to high quality continuing professional development (CPD) is necessary for healthcare professionals to retain competency within the ever-evolving worlds of medicine and health. Most low- and middle-income countries, including Rwanda, have a critical shortage of healthcare professionals and limited access to CPD opportunities. This study scoped the literature using review articles related to the use of information and communication technology (ICT) and video conferencing for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 22 publications
2
39
0
1
Order By: Relevance
“…Along with our results, most of the included studies in a scoping review of the interprofessional online learning for primary healthcare reported that e-learning courses had positive outcomes such as advancement in participants' attitudes, perceptions, knowledge, and skills [26]. Moreover, results of a scoping review of six studies showed that, in continuing professional development programs, both Internet-based and non-Internet-based technology approaches enhanced healthcare professionals' knowledge, skills, and attitudes [3].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Along with our results, most of the included studies in a scoping review of the interprofessional online learning for primary healthcare reported that e-learning courses had positive outcomes such as advancement in participants' attitudes, perceptions, knowledge, and skills [26]. Moreover, results of a scoping review of six studies showed that, in continuing professional development programs, both Internet-based and non-Internet-based technology approaches enhanced healthcare professionals' knowledge, skills, and attitudes [3].…”
Section: Discussionsupporting
confidence: 80%
“…CME is a part of continuing professional development (CPD), which concentrates on improving the knowledge and skills of healthcare professionals [3]. In several investigations, the CME programs have had positive effects on the health professionals' awareness, practice, knowledge, confidence, performance, and skills, the quality and efficiency of the healthcare system, and the patients' outcomes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors note that regardless of the format of CPD, effective activities must be evidence based, interactive, involve some form of self-assessment activity, and multiple exposures to the learning material. 22 Online CPD providers in future should aim to incorporate these factors, to maximise the efficacy of their activities while providing doctors with the benefits of cheaper and more accessible CPD.…”
Section: Theme 4: Workplace Challengesmentioning
confidence: 99%
“…There were no exclusive qualitative studies ( Table 1 ). Most study designs were mixed methods (24/52, 46%) [ 8 , 9 , 12 , 18 , 23 , 26 , 35 , 42 ,​ 43 , 45 , 47 , 50 , 55 , 56 , 61 , 64 , 67 , 71 , 72 ], followed by cross-sectional studies (9/52, 17%) [ 22 , 32 , 39 , 42 , 56 , 59 ].…”
Section: Resultsmentioning
confidence: 99%